Devitalized Autograft Associated with the Vascularized Fibula Graft: Irradiation versus Freezing Methods - Rezende, Luis Guilherme Rosifini Alves; Margatho, Guilherme Leipner; Penno, Ricardo Alberto Lupinacci; Mazzer, Nilton; Engel, Edgard Eduard (Journal of Reconstructive Microsurgery, 2021)
Background Among the alternatives for the management of malignant bone tumors is the “devitalized autograft associated with vascularized fibula graft.” The devitalization process is achieved by pasteurization, irradiation, or freezing. The combination of these grafts has been broadly researched for more than 25 years. However, there is no research currently published comparing the various methods or their respective outcomes.Methods A retrospective study was compiled of 26 devitalized autografts associated with vascularized fibula performed to limb salvage of malignant bone tumors. They were divided into two groups according to the devitalization method: either freezing (12 procedures) or irradiation (14 procedures). Clinical, radiographic, and scintigraphic results were assessed at least 24 months after surgery.Results The union rates reached 83.3% in the freezing group and 92.8% in the irradiated group but did not express different outcomes. Scintigraphic viability was observed in all the grafts that achieved radiographic union (Mann–Whitney U-test: p = 0.005). Three patients had nonunion, with only one having no viability in the scintigraphy (Mann–Whitney U-test: p = 0.001). There was no malignant recurrence in the autograft, only in surrounding soft tissues. Local recurrence was statistically higher in larger tumors (Mann–Whitney U-test: p = 0.025).Conclusion Both groups presented similar union rates and are considered safe to devitalize bone graft despite different outcomes observed. The survivor rates observed could be limited by the existence of the techniques.
Keywords: microsurgery; osteosarcoma; devitalized autograft; combined autografts; vascularized fibula graft